Russia's Grom-2019 strategic nuclear exercise. Issue 9 (21st October 2019) - Unknown
Abstract : Russia's recent nuclear forces exercise was probably its largest since the collapse of the Soviet Union in 1991. Uncertainty remains over the exact number and type of weapons tested. The exercise suggests that nuclear systems remain fundamental to Moscow's approach to deterrence, and can be understood, at least in part, as an attempt to convey to Washington the benefits of extending the New Strategic Arms Reduction Treaty.